2017
DOI: 10.1111/myc.12652
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fungicidal effects of methylene blue at 625‐nm

Abstract: The aim of the study is to confirm the effectiveness of photodynamic therapy (PDT) as a significant inhibitor of Trichophyton rubrum (T. rubrum) and to determine the most appropriate dose and rate of delivery. Trichophyton rubrum is the most common dermatophyte worldwide, responsible for the majority of superficial fungal infections. The traditional treatment of T. rubrum has known adverse effects. An alternative treatment is warranted. Photosensitised T. rubrum specimens were treated with 625-nm light at dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The inhibition rate increased with concentration and light dose with 1.25 μg/mL MB, red light at the dose of over 40 J/cm 2 completely killed all the spores. Guffey et.al 19 found that at MB 2 μmmol/L (about 0.64 μg/mL), the spores of T rubrum were completely killed by 625 nm red light at the dose of 60 J/cm 2 , which is approximately consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The inhibition rate increased with concentration and light dose with 1.25 μg/mL MB, red light at the dose of over 40 J/cm 2 completely killed all the spores. Guffey et.al 19 found that at MB 2 μmmol/L (about 0.64 μg/mL), the spores of T rubrum were completely killed by 625 nm red light at the dose of 60 J/cm 2 , which is approximately consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The present study confirms that MB-PDT has a definite inhibitory effect on T rubrum, which is consistent with previous studies. 19 This study also evaluated the susceptibility of the microspores and hyphae of T rubrum to MB-PDT, respectively. Our results revealed that both spores and hyphae could be successfully inhibited by MB-PDT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, photodynamic therapy has been revealed to be an efficient therapeutic solution against a variety of fungi, including antropophilic, that is, Trichophyton rubrum, and zoophilic, that is, Trichophyton mentagrophytes dermatophytes [30,31]. Several studies have also demonstrated that methylene blue mediated photodynamic therapy has the definite better inhibitory effect on fungi, which solution was tested in detail against T. rubrum [32,33]. Methylene blue is a photosensitiser that has a strong absorption band in the red light wavelength range, presents low toxicity toward human and animal cells, and is relatively inexpensive [34].…”
Section: Introductionmentioning
confidence: 99%
“…PS plays a key role among the three elementary components in aPDT. Previous in vitro studies demonstrated that T rubrum could be effectively killed by a wide variety of PSs including rose bengal (RB), 11 5‐aminolevulinic acid (5‐ALA), 12 curcumin, 13 indocyanine green (ICG), 14 methylene blue (MB), 15 toluidine blue (TBO), 16 hypericin 17 and phthalocyanine 4 (Pc 4) 18 . Several clinical case reports also revealed that 5‐ALA–mediated aPDT could completely cure the onychomycosis and tinea cruris in patients caused by T rubrum 19‐21 …”
Section: Introductionmentioning
confidence: 99%